Potential for Blue-Gray Water Trade-offs for Irrigation in Small Towns of Pakistan: A Case Study of Farmers’ Costs and Benefits in Haroonabad (The Pakistan Development Review, 2002)
The growing demand and the competition for fresh water in various sectors suggest that the irrigated agriculture will have to release freshwater for more important and valuable uses. This implies that other options would need to be identified to meet water demands for agriculture. Meeting irrigation requirements through non-conventional water sources is one of the options for agricultural uses. Gray water use for irrigation, a pervasive practice in urban and peri-urban areas of many developing countries, could be one of the solutions. The debate on wastewater irrigation from an environmental point of view is already on, focussing more on human and environmental “safety” aspects. The “value” aspect of the wastewater irrigation remains neglected, however. The irrigation users of untreated wastewater in many parts of the world had already traded off and revealed their preference for gray over blue water decades ago, when the water supply systems in towns and cities were set up. Why they would do it despite the high environmental and health risks associated with its use needs an answer. The paper documents the costs and benefits of wastewater irrigation from users’ point of view, and assesses the potential for real blue water savings in a small town setting in the southern Punjab, Pakistan. The data presented in the paper suggest that wastewater irrigation does lead to blue water savings, and it is profitable for farmers. While its potential is not fully exploited, more focus on appropriate approaches to physical and institutional aspects of wastewater disposal planning and management could make wastewater irrigation more productive, profitable, and safe for individuals as well as for the society as a whole.